(3eYTQGJ GdMUQjs - (3Ydj Hf YHO GdZfj GdagQj GdMUQj GdbjQhGfj , CHh GdMSf,J (B488 (3g` s
(3ChdgG (B:s
(3bGajI GdCda(B: (3CeGdc jG OGA GdeMH OhGA Hdi YfO HYV GdfGS efc TaGA s
(3BNQgG (B:s
(3jcd hjYji efWbj Yf TcjJj hefWb ZjQ dG cdjd hdG Yj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI ajgG VHWs
(3aj GdZRd hGdfSjH Ydi GdMQhas
(3HBNQgG eG gh aj ZjQ GdCOHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs